The healthy management: the moderator role of transformational leadership on health workers - Grau-Alberola, Ester; Figueiredo-Ferraz, Hugo; López-Vílchez, Jorge Jesús; Gil-Monte, Pedro R. (Anales de Psicología / Annals of Psychology, 2022)
Psychosocial risks arising from work, like workload, have a negative impact on the quality of work life, especially in terms of the deterioration in working conditions and negative consequences for employees’ health. The style of leadership exercised is key in coping with perceived psychosocial risks. The purpose of this study was to analyse the influence of transformational leadership and workload on psychosomatic disorders, and the moderating role of transformational leadership in the relationship between workload and psychosomatic disorders. The sample consisted of 408 Spanish employees working with people with intellectual disabilities. Workload and Psychosomatic disorders were measured by the UNIPSICO subscales, Transformational leadership was measured by a subscale adapted from the Multifactor Leadership Questionnaire (Bass & Avolio, 1989). Carrying out moderation analysis in PROCESS 3.4 results showed that both Workload and Transformational leadership had a significant influence on Psychosomatic disorders. In addition, Transformational leadership moderated the relationship between Workload and Psychosomatic disorders. Transformational leadership buffers the impact of workload on employees’ health and therefore in the need to carry out training programs for managers in organizations in order to exercise a healthy management.